2015
DOI: 10.15789/2220-7619-2015-3-243-252
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiology Acute Intestinal Infections Molecular Monitoring in Children’s Hospital

Abstract: Резюме. На территории РФ в общей структуре острых кишечных инфекций удельный вес вирусных диарей среди детей колеблется в зависимости от сезона от 24 до 78% случаев. Этиологическая расшифровка вирусных острых кишечных инфекций проводится в основном среди пациентов инфекционных стационаров. Вопрос о распространенности вирусных острых кишечных инфекций в неинфекционных стационарах, в том числе как инфекций, связанных с оказанием медицинской помощи, остается недостаточно исследованным. Опреде-ление доли вирусного… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Достаточно широкое внедрение молекулярно-биологических лабораторных методов диагностики внесло существенный вклад в представление об эпидемиологии острых диарей (ОД) и их современной структуре [9,12,22]. В настоящее время в Российской Федерации, как и в других странах, лидерами среди вирусных возбудителей острых диарей, наиболее значимыми по частоте возникновения как спорадической, так и вспышечной заболеваемости, являются ротавирусы и норовирусы [7,8,18,13].…”
Section: Introductionunclassified
“…Достаточно широкое внедрение молекулярно-биологических лабораторных методов диагностики внесло существенный вклад в представление об эпидемиологии острых диарей (ОД) и их современной структуре [9,12,22]. В настоящее время в Российской Федерации, как и в других странах, лидерами среди вирусных возбудителей острых диарей, наиболее значимыми по частоте возникновения как спорадической, так и вспышечной заболеваемости, являются ротавирусы и норовирусы [7,8,18,13].…”
Section: Introductionunclassified
“…At the first stage of the study, it was found that enteric viruses were detected in 43.8% of patients with the syndrome of gastrointestinal dysfunction unrelated to the underlying disease (95% CI 40.1-47.5) [4]. Among the persons infected with enteric viruses, mono-infection was diagnosed in 72% of patients, mixed infection in 28% (p=0.007).…”
mentioning
confidence: 97%
“…Studying different aspects of the problem of acute enteric infections (AEI) of viral etiology is urgent today due to their wide spread, polyetiology, variety of transmission ways and factors, marked seasonality, the continuing upward trend in incidence often acquiring group character and occurring as outbreaks, particularly among pediatric population [1][2][3][4][5][6]. The outbreaks of viral AEI can be also registered in various healthcare institutions specializing in both infectious and noninfectious diseases [1,3,7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation